2015
DOI: 10.1016/j.ymgme.2014.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of agalsidase alfa enzyme replacement in Fabry disease: A Fabry Outcome Survey analysis

Abstract: Outcomes from 5 years of treatment with agalsidase alfa enzyme replacement therapy (ERT) for Fabry disease in patients enrolled in the Fabry Outcome Survey (FOS) were compared with published findings for untreated patients with Fabry disease. Data were extracted from FOS, a Shire-sponsored database, for comparison with data from three published studies. Outcomes evaluated were the annualized rate of change in estimated glomerular filtration rate (eGFR) and left ventricular mass indexed to height (LVMI) as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 23 publications
2
30
0
3
Order By: Relevance
“…For consistency with our previous analysis [6], which compared treated patients from FOS with untreated patients in the published literature [16], the definition of events was broader in our FOS analysis than in the analysis of Germain et al [8], and therefore some of these events were less severe (e.g., transient ischemic attack, prolonged reversible ischemic neurologic deficit). In contrast, Germain et al focused on severe clinical events, which were defined as "chronic dialysis, kidney transplant, myocardial infarction, congestive heart failure, major cardiac procedures (i.e., implantation of a balloon pump, cardioverter-defibrillator or first pacemaker; or bypass surgery), stroke and death" [8].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…For consistency with our previous analysis [6], which compared treated patients from FOS with untreated patients in the published literature [16], the definition of events was broader in our FOS analysis than in the analysis of Germain et al [8], and therefore some of these events were less severe (e.g., transient ischemic attack, prolonged reversible ischemic neurologic deficit). In contrast, Germain et al focused on severe clinical events, which were defined as "chronic dialysis, kidney transplant, myocardial infarction, congestive heart failure, major cardiac procedures (i.e., implantation of a balloon pump, cardioverter-defibrillator or first pacemaker; or bypass surgery), stroke and death" [8].…”
Section: Discussionsupporting
confidence: 57%
“…The current analysis is an extension of our retrospective analysis [6], which found that agalsidase alfa ERT appeared to slow the progression of renal impairment and LVH, and composite morbidity events (including death) occurred later, in FOS patients receiving agalsidase alfa ERT compared with published findings in untreated patients with Fabry disease. The current work represents a purely descriptive analysis of the status of treated patients; because of the lack of external comparator groups, no comparison of agalsidase alfa treated and untreated patients was possible.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The first reports of ERT efficacy on renal outcomes were encouraging [11,90]; reversal of renal glycosphingolipid accumulation in the vasculature and in other renal cell types and decrease of Gb3 in podocytes and distal tubular epithelium were observed after 11 months of agalsidase alfa treatment [91]. From the large international database Fabry Outcome Survey (FOS), several studies have confirmed that treatment with agalsidase alfa stabilizes or minimizes eGFR decline in both male and female Fabry patients [92][93][94][95]. The study by Feriozzi et al [93], in 165 patients followed for 3 years on treatment, also showed how proteinuria influences the loss of eGFR, with an average of 1.68 mL/min/1.73 m 2 /year in patients with baseline proteinuria <0.50 g/day (n = 40) and an average of 3.98 mL/min/1.73 m 2 /year in patients with values >0.50 g/ day (n = 14).…”
Section: Treatment Of Fabry Nephropathymentioning
confidence: 99%
“…Apart from the reported benefits of ERT on kidney function, several studies point to an action of this therapy against progression to cardiac and cerebrovascular complications [12,94,95,99,100]. In fact, risk of morbidity was reduced and survival was improved in treated patients from the FOS database compared to untreated groups from published literature [95]: median age at first composite event (renal, cardiac or stroke event, or death) was greater in agalsidase alfa-treated males and females, at 48 years and 56.9 years, respectively, compared with untreated patients, at 41 years and 53 years, respectively, whereas the estimated median survival time was 77.5 years for male patients from FOS compared with 60 years in patients without ERT.…”
Section: Treatment Of Fabry Nephropathymentioning
confidence: 99%